2002
DOI: 10.1590/s0100-879x2002000300008
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of methods for urinary albumin determination in patients with type 1 diabetes

Abstract: We tested the correlation of the albumin-to-creatinine ratio (A/C) in an early-morning urine sample, measured with a commercial kit (DCA 2000 ® ), with the conventional immunoturbidimetric determination in the laboratory and with overnight albumin excretion rate (reference method). Fifty-five type 1 diabetic adolescents had their first-morning urine collected on the 1st and 8th day of the period. Urinary albumin and creatinine were determined immediately using the DCA 2000 ® kit. Samples were also stored for l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
0
6
0
2
Order By: Relevance
“…4 In humans, microalbuminuria and overt albuminuria are defined as urine albumin concentrations of 2-20 mg/dl and above 20 mg/dl, respectively. 9,12,15 Recent studies 15 validated an ELISA kit designed to measure canine albumin in different biological specimens and showed that pathological albuminuria commonly occurs in dogs, even if the normal range is not well established. Unfortunately, ELISA is time consuming and can hardly be carried out as a routine screening test.…”
mentioning
confidence: 99%
“…4 In humans, microalbuminuria and overt albuminuria are defined as urine albumin concentrations of 2-20 mg/dl and above 20 mg/dl, respectively. 9,12,15 Recent studies 15 validated an ELISA kit designed to measure canine albumin in different biological specimens and showed that pathological albuminuria commonly occurs in dogs, even if the normal range is not well established. Unfortunately, ELISA is time consuming and can hardly be carried out as a routine screening test.…”
mentioning
confidence: 99%
“…Various previous studies also give support towards this factor due to easy collection, low cost and high sensitivity [2,[35][36][37].…”
Section: Discussionmentioning
confidence: 80%
“…Diabetic nephropathy (DN) is the most frequent single cause of end-stage renal disease in many countries [1]. Hyperfiltration and microalbuminuria characterize the clinical stages of DN [2]. Increased levels of albumin in the urine have been clearly established as an important determinant for renal complication of diabetes [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies which compared either FMV or RUS and albuminuria measure such as UAC and/or ACR as alternative to measurement of 24-h UAE [21][22][23][24][25][26][27]. Few studies correlated ACR in either single FMV or RUS [17,28,29].…”
Section: Discussionmentioning
confidence: 99%